Where sky meets sea: Integrated aerosol and ocean color retrieval from PACE SPEXone multi-angle polarimetry - Meng Gao; Kamal Aryal; Peng-Wang Zhai; Kirk Knobelspiesse; Bryan Franz; Brian Cairns; Ivona Cetinić; Guangliang Fu; Otto Hasekamp; Amir Ibrahim; Andrew M. Sayer; P. Jeremy Werdell (Remote Sensing of Environment, 2026)

Advancing Earth System Science With the NASA Plankton, Aerosol, Cloud, Ocean Ecosystem ( PACE ) Satellite Mission - P. Jeremy Werdell; Brian Cairns; Skyelar A. Caplan; Ivona Cetinić; Sean R. Foley; Bryan A. Franz; Meng Gao; Zachary T. Fasnacht; K. Fred Huemmrich; Amir Ibrahim; Kirk D. Knobelspiesse; Antonio Mannino; et al. (Global Change Biology, 2026)
Earth observation satellites transform our understanding of Earth's biological, atmospheric, and surface systems. The Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) mission, launched in 2024, represents NASA's latest investment in multidisciplinary Earth system science, building upon multi‐decadal heritage while introducing revolutionary capabilities. Since launch, PACE has extended and improved upon NASA's 30+ years of global satellite observations of our living ocean, atmosphere, and land, and initiated an advanced set of climate‐ and applications‐relevant data records. Mission goals include extending and improving upon systematic ocean color, aerosol, cloud, and terrestrial data records for Earth system studies, and addressing emerging science questions related to socioeconomic applications. PACE helps assess ocean health by determining the distribution of aquatic phytoplankton. In doing so, it is the first mission to provide daily, global measurements that will enable prediction of the “boom‐bust” cycle of fisheries, the appearance of harmful algae, and other factors that affect commercial and recreational industries. PACE also observes clouds and tiny airborne particles known as aerosols that influence air quality and absorb and reflect sunlight, thus warming and cooling the atmosphere. Many stakeholders rely on these key data to forecast weather, visibility, and air quality. Also, PACE provides novel and near‐daily views of land surfaces, collectively extending heritage vegetation time series while introducing novel terrestrial measurements previously only achievable at local scales. PACE ultimately provides observations that benefit Earth system research and society as a whole in ways that other current satellites cannot. As it passes its two‐year anniversary, the mission exemplifies how combining hyperspectral radiometry with multi‐angle polarimetry enables transformative Earth system science, addressing critical uncertainties while establishing new paradigms for integrated observations of our changing planet. This review examines how PACE fills critical gaps across aquatic, terrestrial, and atmospheric science disciplines.

Opportunities and challenges for use of minipigs in nonclinical pharmaceutical development: Results of a follow-up IQ DruSafe survey - David O. Clarke; Kaushik Datta; Kevin French; Michael W. Leach; Drew Olaharski; Susanne Mohr; Devon Strein; Jeanine Bussiere; Bianca Feyen; Beatrice E. Gauthier; Michael Graziano; Joanna Harding; et al. (Regulatory Toxicology and Pharmacology, 2024)

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

Foliage re-establishment of Pinus palustris Mill. saplings after spring or fall prescribed fire - Mary Anne S. Sayer; Michael C. Tyree; Dylan N. Dillaway; Brian M. Rudd (New Forests, 2018)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)